2005
DOI: 10.1007/s00436-005-1433-4
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of the salivary glands of Rhodnius domesticus Neiva & Pinto, 1923 (Hemiptera: Reduviidae) by Trypanosoma rangeli Tejera, 1920 (Protozoa: Kinetoplastida)

Abstract: Penetration of the heteroxenous protozoan Trypanosoma rangeli into the salivary glands of its invertebrate host Rhodnius domesticus has been investigated here using different approaches. Electron microscopy showed that epimastigotes coming from the insect hemocoel cross the basal lamina that surrounds the salivary glands and penetrate through the gland cells cytoplasm. After reaching the gland lumen, epimastigote forms remain adhered to the gland cell microvilli by their flagella, while metacyclic trypomastigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In the trypanosomatid-insect interactions, the adhesion to host tissue seems to occur mainly through the flagella [37][40], and binding through the cellular body is rarely observed [41], [42]. In contrast with a previous study that showed Trypanosoma rangeli invading Rhodnius prolixus salivary glands with the flagellum foremost [27], the passage of P. serpens parasites through the basal lamina of O. fasciatus salivary gland occurred through the cellular body. In addition, the invasion of several parasites in an area with altered morphology and the presence of suggestive lesions were observed.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the trypanosomatid-insect interactions, the adhesion to host tissue seems to occur mainly through the flagella [37][40], and binding through the cellular body is rarely observed [41], [42]. In contrast with a previous study that showed Trypanosoma rangeli invading Rhodnius prolixus salivary glands with the flagellum foremost [27], the passage of P. serpens parasites through the basal lamina of O. fasciatus salivary gland occurred through the cellular body. In addition, the invasion of several parasites in an area with altered morphology and the presence of suggestive lesions were observed.…”
Section: Discussionmentioning
confidence: 59%
“…The salivary glands of the infected insects were obtained by gently pulling off their heads [27]. Parasite adhesion to the outer surface of the salivary glands was observed by SEM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms involved in adhesion to a substrate in T. brucei (Ersfeld & Gull 2001) T. cruzi (Ferreira et al 2008) and T. rangeli (Meirelles et al 2005) require the crucial and active participation of the flagella of these parasites. During metacyclogenesis, the flagellar membrane remains connected to the epithelial surface (Ersfeld & Gull 2001) representing an important interface between the parasite and its host that is essential for the fulfilment of its biological cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the cells is still not completely known. In Rhodnius domesticus, Meirelles et al (2003) showed that the main salivary glands have mononuclear cells, whereas Anhê et al (2007) described binucleated cells in both the main salivary gland and the accessory gland from R. prolixus and Rhodnius neglectus.…”
mentioning
confidence: 99%